The appointment of female mufti in Malaysia: An analysis on the views of Fatwa members and Syariah experts - Irwan Mohd Subri; Ahmad Wifaq Mokhtar; Azman Ab. Rahman; Hishomudin Ahmad; Norzulaili Mohd Ghazali; Halil, Nur Fatin (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA